The mechanism of action of a novel neuroprotective low molecular weight dextran sulphate: New platform therapy for neurodegenerative diseases like Amyotrophic Lateral Sclerosis - Logan, Ann; Belli, Antonio; Di Pietro, Valentina; Tavazzi, Barbara; Lazzarino, Giacomo; Mangione, Renata; Lazzarino, Giuseppe; Morano, Inés; Qureshi, Omar; Bruce, Lars; Barnes, Nicholas M.; Nagy, Zsuzsanna (Frontiers in Pharmacology, 2022)
Background: Acute and chronic neurodegenerative diseases represent an immense socioeconomic burden that drives the need for new disease modifying drugs. Common pathogenic mechanisms in these diseases are evident, suggesting that a platform neuroprotective therapy may offer effective treatments. Here we present evidence for the mode of pharmacological action of a novel neuroprotective low molecular weight dextran sulphate drug called ILB®. The working hypothesis was that ILB® acts via the activation of heparin-binding growth factors (HBGF). Methods: Pre-clinical and clinical (healthy people and patients with ALS) in vitro and in vivo studies evaluated the mode of action of ILB®. In vitro binding studies, functional assays and gene expression analyses were followed by the assessment of the drug effects in an animal model of severe traumatic brain injury (sTBI) using gene expression studies followed by functional analysis. Clinical data, to assess the hypothesized mode of action, are also presented from early phase clinical trials. Results: ILB® lengthened APTT time, acted as a competitive inhibitor for HGF-Glypican-3 binding, effected pulse release of heparin-binding growth factors (HBGF) into the circulation and modulated growth factor signaling pathways. Gene expression analysis demonstrated substantial similarities in the functional dysregulation induced by sTBI and various human neurodegenerative conditions and supported a cascading effect of ILB® on growth factor activation, followed by gene expression changes with profound beneficial effect on molecular and cellular functions affected by these diseases. The transcriptional signature of ILB® relevant to cell survival, inflammation, glutamate signaling, metabolism and synaptogenesis, are consistent with the activation of neuroprotective growth factors as was the ability of ILB® to elevate circulating levels of HGF in animal models and humans. Conclusion: ILB® releases, redistributes and modulates the bioactivity of HBGF that target disease compromised nervous tissues to initiate a cascade of transcriptional, metabolic and immunological effects that control glutamate toxicity, normalize tissue bioenergetics, and resolve inflammation to improve tissue function. This unique mechanism of action mobilizes and modulates naturally occurring tissue repair mechanisms to restore cellular homeostasis and function. The identified pharmacological impact of ILB® supports the potential to treat various acute and chronic neurodegenerative diseases, including sTBI and ALS.